Cellular Up-regulation of Nedd4 Family Interacting Protein 1 (Ndfip1) using Low Levels of Bioactive Cobalt Complexes - Schieber, Christine (American Society for Biochemistry and Molecular Biology, 2011)
The delivery of metal ions using cell membrane-permeable metal complexes represents a method for activating cellular pathways. Here, we report the synthesis and characterization of new [Co(III)(salen)(acac)] complexes capable of up-regulating the ubiquitin ligase adaptor protein Ndfip1. Ndfip1 is a neuroprotective protein that is up-regulated in the brain after injury and functions in combination with Nedd4 ligases to ubiquitinate harmful proteins for removal. We previously showed that Ndfip1 can be increased in human neurons using CoCl(2) that is toxic at high concentration. Here we demonstrate a similar effect can be achieved by low concentrations of synthetic Co(III) complexes that are non-toxic and designed to be activated following cellular entry. Activation is achieved by intracellular reduction of Co(III) to Co(II) leading to release of Co(II) ions for Ndfip1 up-regulation. The cellular benefit of Ndfip1 up-regulation by Co(III) complexes includes demonstrable protection against cell death in SH-SY5Y cells during stress. In vivo, focal delivery of Co(III) complexes into the adult mouse brain was observed to up-regulate Ndfip1 in neurons. These results demonstrate that a cellular response pathway can be advantageously manipulated by chemical modification of metal complexes, and represents a significant step of harnessing low concentration metal complexes for therapeutic benefit.